2022
DOI: 10.1177/15344843211068807
|View full text |Cite
|
Sign up to set email alerts
|

Research Topics and Collaboration in Human Resource Development Review 2012–2021: A Bibliometrics Approach

Abstract: In celebrating HRDR’s 20 years of publication, this study aims to shed light on research trends in the journal and future research needs by examining 10 years of publications from a structural perspective. We used three complementary computational methods to find major research trends and themes including keyword network analysis, topic modeling, and bibliographic coupling. This paper presents the findings on the research themes, structural coherence, and semantic relevance based on clusters formed by normaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 48 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Five HRD journals ( Advances in Developing Human Resources , European Journal of Training and Development , HRDI , Human Resource Development Quarterly , and HRDR ) publish articles on: formal/informal/organizational learning, training & development, career development, organization development, leadership development, learning/training transfer, diversity, critical HRD, and technology (Cho & Zachmeier, 2015; Shirmohammadi et al, 2021; Yoon & Chae, 2022), all of which are common HRD topics at individual, team, and organizational levels but not beyond. There is a strong need to expand the boundary-spanning HRD research to fill the gap between research and practice through embracing more socially and globally impactful and actionable research topics for theory building in HRD.…”
Section: What We Are Missingmentioning
confidence: 99%
See 1 more Smart Citation
“…Five HRD journals ( Advances in Developing Human Resources , European Journal of Training and Development , HRDI , Human Resource Development Quarterly , and HRDR ) publish articles on: formal/informal/organizational learning, training & development, career development, organization development, leadership development, learning/training transfer, diversity, critical HRD, and technology (Cho & Zachmeier, 2015; Shirmohammadi et al, 2021; Yoon & Chae, 2022), all of which are common HRD topics at individual, team, and organizational levels but not beyond. There is a strong need to expand the boundary-spanning HRD research to fill the gap between research and practice through embracing more socially and globally impactful and actionable research topics for theory building in HRD.…”
Section: What We Are Missingmentioning
confidence: 99%
“…Reaction toWang and Doty (Russ-Eft, 2022) 2. Reaction to Wang and Doty(Yoon, 2022) 3. Reaction toWang and Doty (Poell, 2022) 4.…”
mentioning
confidence: 99%
“…From Kahn's theory to contemporary business practice, the essence of the engagement discussion has inherently relied on employee performance and organization development, which resonates strongly with the target of HRD. Thus, it is not surprising that engagement is positioned at the center of HRD research and practice (Yoon & Chae, 2022), and vice versa.…”
Section: Situating Human Resource Development In Employee Engagementmentioning
confidence: 99%
“…The picture becomes more unsettling if we look closer at who is publishing in major HRD journals. Research collaboration observed in papers published at HRD journals has been centered in the U.S. and Europe, and no partnership has existed among scholars outside the U.S. (Yoon & Chae, 2022). Even when I have seen many non-US authors’ papers in the literature, they, including me, were from doctoral programs in the U.S.…”
Section: Reflection On Absences Symbolic Power and Symbolic Violence ...mentioning
confidence: 99%